If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18.6 + -2x = 3x + -2.5 Reorder the terms: 18.6 + -2x = -2.5 + 3x Solving 18.6 + -2x = -2.5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 18.6 + -2x + -3x = -2.5 + 3x + -3x Combine like terms: -2x + -3x = -5x 18.6 + -5x = -2.5 + 3x + -3x Combine like terms: 3x + -3x = 0 18.6 + -5x = -2.5 + 0 18.6 + -5x = -2.5 Add '-18.6' to each side of the equation. 18.6 + -18.6 + -5x = -2.5 + -18.6 Combine like terms: 18.6 + -18.6 = 0.0 0.0 + -5x = -2.5 + -18.6 -5x = -2.5 + -18.6 Combine like terms: -2.5 + -18.6 = -21.1 -5x = -21.1 Divide each side by '-5'. x = 4.22 Simplifying x = 4.22
| -42=3(x-4) | | (b-4)(3b+2)= | | -19.8+11z=16.84+10.86+16z | | 0.012000/48 | | -2x-9+5x=15 | | a+(-12)=-9 | | 21!/17!4! | | -4x+28=4(x-5) | | 6x+26=92 | | 0.3w=7.1w+18.36 | | 1x+9=4x-6 | | -8x-13=-5x-10 | | 9x6y5/3xy2 | | 4x+16=3x+10 | | 5(2x+4)-9=-49 | | 9.32-14.6h=-16.1-18.7h | | 4(3x-2)=4x-48 | | 2a+9=3a+5 | | 13.97-9.2s+12.62=-11.8s-19.95 | | 2(4x+5)=3x-40 | | -17-15c=-15c+1-6 | | -22=2(x-1) | | 5(x+4)-6=9 | | 4-7x=1+2x | | 1-0.8451x-0.1373x^2=0 | | 10p-13=-p+15+13p | | 4k-7=-17+3k | | 2x-10=2(3x-3) | | 4(5x+1)=-5(5x-4) | | 7x+27=3x+31 | | -16j=-12-17j | | 15j=-12+19j |